Meta-analysis of cinacalcet plus calcitriol for the treatment of secondary hyperparathyroidism in hemodialysis patients - Feng Hui-ling; Zhang Lian; Zhang Jin-ming; Wu Xiao-yan (Linchuang shenzangbing zazhi)
ObjectiveTo evaluate the efficacy and adverse reactions of cinacalcet plus calcitriol in the treatment of secondary hyperparathyroidism in hemodialysis patients.MethodsClinical trial of cinacalcet plus calcitriol in the treatment of secondary hyperparathyroidism in dialysis patients were retrieved from the databases of PubMed，Embase，Cochrane Library，China National Knowledge Internet，Wangfang and VIP.Two researchers independently screened the literatures and extracted the relevant data according to Cochrane Systematic Evaluator's Manual 5.1.0.The included randomized controlled trials were Meta-analyzed by RevMan5.3 software.ResultsA total of 30 articles were retrieved.The total sample size was 2497 people.Meta-analysis indicated that the effective rate of combined drug group significantly improved as compared with single drug group.And the effects of reducing the levels of serum phosphorus concentration，alkaline phosphatase，fibroblast growth factor 23 and parathyroid hormone and lowering parathyroid volume were more significant.The incidence of adverse reactions was lower in combined drug group than that in single cinacalcet group and there was no difference with single calcitriol group.The level of serum calcium was higher in combined drug group than single cinacalcet group and lower than that in single calcitriol group.The level of serum calcium-phosphorus product was higher in combined drug group than single cinacalcet group and lower than that in single calcitriol group.ConclusionBased upon current evidence，cinacalcet plus calcitriol in the treatment of secondary hyperparathyroidism offers a better clinical efficacy and a lower incidence of adverse reactions as compared with single medication in hemodialysis patients.